2019
DOI: 10.1177/1744259119863446
|View full text |Cite
|
Sign up to set email alerts
|

Influence of envelope thickness and solar absorptivity of a test cell on time lag and decrement factor

Abstract: This work deals with the influence of envelope thickness and solar absorption on the time lag and the decrement factor. For this, a test cell of 1 m3 of volume is built with a material commonly used in construction in Senegal, the compressed earth brick stabilized with cement. The ambient-air temperature inside and outside of test cell and solar direct normal irradiance is measured. The test cell is modeled using EnergyPlus software. The comparison of experimental and theoretical ambient-air temperature puts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…were found only for CEB 0.14 m and CEB 0.20 m where time lag increase a little with values between 4-5 h. However for other simulation cases, time lag values were less than 2 h. In fact, the more the thermal mass or insulation thickness, the less the heat conduction through the building wall. As mentioned [13] beyond 32 cm, the indoor environment is no longer influenced by the outdoor thermal flux through walls. This explains why the effect of thermal mass on thermal lag is more pronounced for thicknesses 0.14 m and 0.22 m; and not 0.35 m and 0.50 m. Because insulation and CEB 0.35 m and CEB 0.50m hinder heat conduction through walls, the low values of thermal lag obtained are related to direct daytime heat gains through the building's other components, especially openings and roof.…”
Section: Simulation Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…were found only for CEB 0.14 m and CEB 0.20 m where time lag increase a little with values between 4-5 h. However for other simulation cases, time lag values were less than 2 h. In fact, the more the thermal mass or insulation thickness, the less the heat conduction through the building wall. As mentioned [13] beyond 32 cm, the indoor environment is no longer influenced by the outdoor thermal flux through walls. This explains why the effect of thermal mass on thermal lag is more pronounced for thicknesses 0.14 m and 0.22 m; and not 0.35 m and 0.50 m. Because insulation and CEB 0.35 m and CEB 0.50m hinder heat conduction through walls, the low values of thermal lag obtained are related to direct daytime heat gains through the building's other components, especially openings and roof.…”
Section: Simulation Discussionmentioning
confidence: 97%
“…Secondly, when the numerical model precision is acceptable, the sensitivity analysis is performed and the influence of 4 different parameters involved is found with acceptable accuracy. Toure et al [13] investigated the influence of envelope thickness and solar absorptivity on time lag and decrement factor using this approach. They found that increasing wall thickness improve the thermal inertia effects as decrement factor and time lag.…”
Section: Introductionmentioning
confidence: 99%
“…Further research has shown that compressed earth blocks are more durable than adobe materials [51,52] and provide the same or greater thermal response than concrete in warm locations [51,[53][54][55]. Toure et al [56] studied the effect of envelope thickness and solar absorption on time lag and decrement factor. They discovered that a thicker wall improves thermal inertia effects such as decrement factor and time lag.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By contrast, the difference between T sa and T e could be too small for walls of very light colours. The choice of the α-value deserves a separate study (see for instance Toure et al, 2020) and will not be addressed here.…”
Section: Study Area Measurements and Assessed Wallsmentioning
confidence: 99%